Creation, opening and maintenance of first literacy schools in Tarifa from de 1813 to 1868 - Criado Atalaya, Juan Antonio (Avances en Supervisión Educativa, 2015)
We are approaching in this work to the first literacy schools which have existed in Tarifa during the XIX Century. Education in this town looked loss-making in the facilities due to several factors. On one hand, the negative repercussion that had the Independence War in the population’s life and the misery that it left, especially in the most popular sectors. On the other hand, it was due to the fact of the abandon of this education service. The first Spanish liberal governments tried to put order in this situation and, thus, it got rid of the Council archives from the Liberal Triennium but it is principally during the reign of Isabel II of Spain in the “Ley Moyano” (Moyano Educational Law) when some references about a bigger normalization of these schools appeared in the Council archives. It spread in the decade of 1860 to the districts. The school located in the ancient granary is the architectonical reference since middle 1800’s.